Teachers’ Conceptions of Teaching Chinese Descriptive Composition With Interactive Spherical Video-Based Virtual Reality - Chen, Mengyuan; Chai, Ching-Sing; Jong, Morris Siu-Yung; Jiang, Michael Yi-Chao (Frontiers in psychology, 2021)
Phenomenographic research about teachers’ conception of teaching has consistently revealed that teachers’ conception of teaching influence their classroom practices, which in turn shape students’ learning experiences. This paper reports teachers’ conceptions of teaching with regards to the use of interactive spherical video-based virtual reality (ISV-VR) in Chinese descriptive composition writing. Twenty-one secondary teachers in Hong Kong involved in an ISV-VR-supported Chinese descriptive writing program participated in this phenomenographic study. Analyses of the semi-structured interviews establish seven conception categories that are specifically related to the use of ISV-VR for descriptive Chinese composition writing: (1) offering students more observational opportunities; (2) improving students’ writing skills; (3) promoting students’ learning participation and motivation; (4) shifting learning from teacher-centric to student-centric, (5) enhancing collaborative learning among students; (6) cultivating students’ positive values and moral character, and (7) shaping students’ self-identity as “writers.” The concurrent and convenient access to the ISV-VR resources was for the teachers an enriched and supportive environment for them to cultivate students’ writer identity. In addition, it was discovered that the structural relationships of the conceptions may be better organized along three axes of continuum: conception’s orientation, teaching attention locus, and understanding of writing. These categories form a hierarchy from skill-oriented to community-oriented, and finally to identity-oriented conception. The findings may provide researchers and practitioners with novel insight into the teaching of composition writing in the contexts of L1 acquisition supported by virtual reality technology.